SYARIâAT ISLAM DAN HUKUM POSITIF DI INDONESIA - Hadjar, Ibnu (Islamic University of Indonesia, 2006)
The formalization of Islamic Shariâah in the system of Indonesian law needs long term. This formalization emerges a crucial problems. Historically, fact shows that Indonesian Moslems have great desire to apply Islamic Shariâah since the arriving Islam in Indonesia, in the era of colony either in Dutch and Japan. Entering the independence of Indonesian era there are several controversies and debates among the founding fathers of Indonesia regarding the foundation of Indonesian state. In this sense, the founding fathers of Indonesian can be classified into the nationalist Moslem and the nationalist secular. Kata kunci: formalisasi, syariâat Islam, hukum positif, dan sejarah.